Mapping of the gene specifying aminoglycoside 3'-phosphotransferase II on the Pseudomonas aeruginosa chromosome. - Okii, M (1983)
We examined the aminoglycoside inactivation enzymes in Pseudomonas aeruginosa strains, seven clinical isolates and seven laboratory strains without plasmids. All strains were found to possess the enzyme aminoglycoside 3'-phosphotransferase II [APH(3')-II]. We isolated an APH(3')-II-deficient mutant from a PAO strain by mutagenesis with N-methyl-N'-nitro-N-nitrosoguanidine. By plasmid (FP5 or R68.45)-mediated conjugation, we determined the locus of the gene specifying the APH(3')-II between trp-6 and pro-82 on the PAO chromosome and designated this gene aphA. It was concluded that the intrinsic resistance of P. aeruginosa to kanamycins, neomycins, paromomycins, ribostamycin, and butirosins was due to this newly determined gene.